(untitled) (ESMAT Magazine, 2019)
It’s an exploratory research that, using the deductive method, makes the education evident as an important adjunct of the Judiciary for the justice access by the people underthejurisdiction, through formation, training and improvement of magistrates and servers through Judicial Schools, specifically in relation to the Tocantins Magistrature Superior School (ESMAT). A quantitative approach will be used, analysing essential matters, how human rights are fundamental to the justice access, and its normative prediction in international and internal scope; justice access by the Judiciary; education offered by the Judiciary to magistrates and servers; ESMAT contributions to justice access. Correlated legislation, institutional data and specialized doctrine will be properly analysed for the preparation of the research.